Clinical features and therapeutic challenges of psoriatic arthritis coexisting with antisynthetase syndrome: a case report and literature review - Yan, Rui; Ke, Dan; Zhang, Yan; Li, Li; Liu, Yanying; Li, Shengguang; Liu, Xiaomin (Frontiers in Immunology, 2025)
ObjectiveThe coexistence of psoriatic arthritis (PsA) with inflammatory myopathies, including antisynthetase syndrome (ASS), is exceptionally rare and presents significant diagnostic and therapeutic challenges. This study reports a case of PsA overlapping with ASS and reviews the literature to analyze clinical features, immunopathogenesis, and treatment strategies.MethodsA 52-year-old female with a 10-year history of psoriasis developed PsA and later presented with muscle weakness, mechanic’s hands, and interstitial lung disease (ILD). Serological testing revealed anti-Jo-1 and anti-SSA/Ro52 positivity, confirming ASS. We compare our case with 17 previously reported cases of psoriasis or PsA coexisting with inflammatory myopathies, highlighting similarities and differences in clinical presentation and treatment response.ResultsPsoriasis and inflammatory myopathies share immunopathogenic pathways, including the IL-17/IL-23 axis, type I interferons, and TNF-α. Therapies effective for psoriasis/PsA, such as TNF and IL-17 inhibitors, may exacerbate inflammatory myopathies, while JAK inhibitors and corticosteroids appear more effective in managing overlap cases. Our patient achieved sustained remission with baricitinib and low-dose prednisone after multiple treatment adjustments.ConclusionPsA and inflammatory myopathies can coexist, requiring careful differentiation and tailored immunomodulatory therapy. Clinicians should recognize overlapping features and optimize treatment to prevent exacerbations. Further research is needed to establish standardized management strategies for this rare overlap syndrome.